PGSD FKIP UNRI STUDENTS’ ATTITUDES IN ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Latifah Hidayati; Guslinda; Zufriady (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The virus is currently spreading around the world and has been labeled as a pandemic by the World Health Organization (WHO). Every activity is conducted at home, which is called Work From Home (WFH). The transition in the educational system from direct to online learning does certainly influence people’s attitudes, which are the indicator of successful learning. It includes knowledge, comprehension, attitudes, and so on. Based on the description, it was conducted the research entitled